"You can't make me do it!" A model of consumer compliance. Issue 1 (10th March 2022) - Bharti, Vijay Payal; Gratz, Elizabeth T.; Fitzgerald, M. Paula
Abstract: Consumer well‐being often depends on compliance with service setting rules and product/service use guidelines. This issue came to the forefront during the COVID‐19 pandemic. Here, we propose and test a compliance model in the context of COVID‐19 social distancing guidelines. Although COVID mitigation is politicized, we fully mediate the impact of political ideology with three constructs: (1) consumer perception that freedom is restricted, (2) complacency, and (3) perceived ethicality. We suggest specific tools that help bypass the political polarization that has occurred in the pandemic. The model can be applied to other areas in which compliance is key to consumer well‐being, such as enforcing age‐related restrictions on purchases and safety‐related behaviors.